If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(x + 30) = -196 Reorder the terms: 14(30 + x) = -196 (30 * 14 + x * 14) = -196 (420 + 14x) = -196 Solving 420 + 14x = -196 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-420' to each side of the equation. 420 + -420 + 14x = -196 + -420 Combine like terms: 420 + -420 = 0 0 + 14x = -196 + -420 14x = -196 + -420 Combine like terms: -196 + -420 = -616 14x = -616 Divide each side by '14'. x = -44 Simplifying x = -44
| v/9-5=(-6) | | z2=9/16 | | 19=-9(8c-3) | | 7v+1+6v= | | 2g+2g-4=43 | | 3-3(x-4)=-3-2 | | b/9=3 | | -3(x+7)=6x-39 | | -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 | | 0.166666667x=4 | | 15y+9x=30 | | 8y+7=9y-1 | | 52=4(s-67) | | 5-5cosx=0 | | 9*b+4=7 | | -26-49= | | -8(-3-2n)=104 | | -7+2(1-5s)=35 | | 9*-b+4=7 | | p/3=1/8 | | 13y-7y=18 | | 81/9*(10-1)=x |